Perbedaan pH Saliva Sebelum dan Setelah Berkumur dengan Rebusan Bunga Rosella pada Mahasiswa Jurusan Keperawatan Gigi Bukittinggi - Zulfikri Zulfikri; Fiki Rivaldo Putra (Jurnal Sehat Mandiri, 2019)
Polyphenols and flavonoids of roselle ( Hibiscus sabdariffa L ) acts as an antiviral, antioxidant and antibacterial that can affect bacteria and increase the pH of saliva in the oral cavity. The purpose of this study to determine differences in the pH of saliva before and after rinsing with stew rosella The design is a quasi-experimental study with pretest and posttest. The population in this study Dental students from the Department of Nursing. The sampling technique is purposive sampling. Data collected by direct observation and examination of the salivary pH. Analysis of the data used using paired t test.Results showed before rinsing with rosella flower stew, average salivary pH 6.6 (acidic) and after rinsing with rosella flower stew average salivary pH to 7.0 (neutral). Statistical test Paired t test showed p value = 0.00 <0.05. Conclusion of the study that there is a significant difference between the pH of saliva before and after rinsing with stew rosella. Suggested to the research subjects to use a mouthwash of natural materials such as stew rosella to maintain oral health.